The Influence of Cerebral Arterial Circle on Prominent Hypointense Vessel Signs in Patients With Internal Carotid Artery Occlusion - Yang, Lei; Yu, Ling; Qin, Wei; Li, Yue; Yang, Shuna; Li, Xuanting; Hu, Wenli (Frontiers in Neurology, 2022)
Background and Purpose— Previous studies on the presence of asymmetrical prominent cortical and medullary vessel signs (APCV/APMV) and collateral circulation in patients with internal carotid artery occlusion ICAO are rare, and the conclusions are inconsistent. Our study aimed to investigate the relationship between the presence of APCV/APMV and collateral circulation in patients with ICAO. Methods— Acute ischemic stroke patients with ICAO were recruited in this study. All 74 patients were divided into two groups depending on the presence of APCV and APMV. The status of cerebral arterial circle (CAC) was graded as poor or good. The poor CAC was defined as MCA was invisible. Severe stroke was defined as cerebral watershed infarction (CWI) or territorial infarction (TI). Clinical and radiologic markers were compared between these two groups. Logistic regression was used to investigate the association between the APCV/APMV and clinical and radiologic markers. Results— A total of 74 patients with ICAO were enrolled. Forty-three patients (58.1%) presented with an APCV and APMV was founded in 35 (47.2%) patients. Compared to patients with non-APCV, patients with APCV had more severe stroke (P= 0.038) and had significantly higher incidence of poor CAC (P=0.022) than those with APCV. Patients with APMV had more severe stroke (P= 0.001). Logistic regression showed that poor CAC was independently associated with APCV and severe stroke were independently associated with APMV. Conclusions— Our study demonstrates that poor CAC was independently associated with the presence of the APCV in patients with ICAO. Severe stroke was independently associated with the APMV.